2023
DOI: 10.1097/hep.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

P4HA2 induces hepatic ductular reaction and biliary fibrosis in chronic cholestatic liver diseases

Abstract: Backgrounds: Prolyl-4-hydroxylases (P4Hs) are key enzymes in collagen synthesis. The P4HA subunit (P4HA1, P4HA2, and P4HA3) contains a substrate binding and catalyzation domain. We postulated that P4HA2 would play a key role in the cholangiocyte pathology of cholestatic liver diseases. Methods: We studied humans with primary biliary cholangitis (PBC) and Primary sclerosing cholangitis (PSC), P4HA2-/- mice injured by DDC, and P4HA2-/-/MDR2-/- double knockout mice. A parallel study was performed in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recent cancer-related studies have determined that certain proteins ( e.g. , BCL-2, P4HA2) interact with SAV1, leading to its ubiquitination and proteasomal degradation 32 , 33 . However, the regulatory molecules for SAV1 in RA FLSs remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cancer-related studies have determined that certain proteins ( e.g. , BCL-2, P4HA2) interact with SAV1, leading to its ubiquitination and proteasomal degradation 32 , 33 . However, the regulatory molecules for SAV1 in RA FLSs remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The DDC-induced mouse model is a classic chronic cholestatic animal model ( Fickert et al, 2007 ; Li et al, 2021 ). The main features of this model are bile duct reaction, hepatic inflammation, and fibrosis ( Arino et al, 2023 ; Zhang et al, 2023 ). In our previous studies, the blood biochemical indicators and liver tissue pathomorphology of mice induced by diet containing 0.025% DDC at 2, 4, 6, and 8 weeks were investigated ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…DDC-fed (0.1%) mice are a xenobiotic- induced mouse model of cholangiopathy. It can induce reactive cholangiocytes, biliary inflammation, pericholangitis, periductal fibrosis, and ultimately portal-portal bridging affecting large bile ducts, which more closely resembles human sclerosing cholangitis and biliary fibrosis[ 34 , 35 ]. In the present study, using this experimental model of mice, we found that we demonstrate that a single dose of rAAV8-mediated inhibition of let-7a can protect mice from hepatic (biliary) injuries, biliary inflammation, proliferation, and fibrosis in experimental sclerosing cholangitis for 2 wk and 6 wk, suggesting that inhibition let-7a delivered by rAAV8 provides a potential therapeutic strategy for sclerosing cholangitis (Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%